Approaches to forensic classification of criminal offences against justice - Sup, Yevhen (Archives of Criminology and Forensic Sciences, 2024)
The lack of scientific development of issues related to the forensic classification of criminal offenses against justice has necessitated an indepth study of these questions. The aim of this article is therefore to develop a forensic classification of criminal offences against justice. Based on the generalization of developments by criminal law specialists and criminologists, the author proposes a classification of criminal offences against justice based on the type of criminal activity. This classification distinguishes between basic criminal offences, related offences, connected offences and other criminal offences. Other criminal offences are clearly distinguishable from these groups, as they are committed by professionals involved in the judicial process. Given the complexity of the investigator’s cognitive activity in these criminal offenses, the author identifies prospects for future research such as the development of scientifically sound recommendations for investigating criminal offenses against justice committed by professional participants in court proceedings.